Effects of Irrigation Schedule and Phosphorus Fertilizer Rates on Forage Yield of Two Cowpea Varieties in Nigeria - Bala, A. G.; Hassan, M. R.; Tanko, R. J.; Hassan, A. H.; Bature, M.S.; Mohammed, A.; Alhabib, I. K.; Salihu, A.I. (Nigerian Journal of Animal Science and Technology (NJAST), 2021)
A field experiment was conducted to evaluate the effects of irrigation schedule and phosphorus fertilizer rates on forage yield of two cowpea varieties during 2018 and 2019 dry season. The experiment was laid out in a 2×3×3 factorial arrangement in a split plot design with three replications. Treatments consisted of 2 cowpea varieties (SAMPEA 14 and 15), 3 irrigation schedule (5, 10 and 15-days) and 3 phosphorus (P) fertilizer rates (0, 20 and 40 kg/ha). Leaf area index, fresh forage yield and dry forage yield were recorded. Results indicated that Leaf area index (LAI), dry forage yield (DFY) and fresh forage yield (FFY) of two cowpea varieties were affected (P<0.05) by some of the treatments during the two years trial. SAMPEA 14 had higher (P<0.05) FFY (4.31 Vs 3.65 t/ha) and DFY (3.13 Vs 2.86 t/ha) compared to SAMPEA 15. There was 4% (0.12t/ha) increase in DFY of Sampea 14 compared to Sampea 15 over the two trial periods. The 15 day irrigation schedule had lower (P<0.05) LAI compared to the other irrigation schedules that were similar. A combined mean for FFY of 4.40 t/ha and DFY of 3.50 t/ha were recorded at irrigation schedule of 5 days interval. DFY increased by 46% (1.61t/ha) in the combined trial periods with respect to the 5 days irrigation schedule compared to the 15 days. The results also revealed that 20 kgP/ha fertilizer rate resulted in higher (P<0.05) FFY and DFY only when compared to the control. The DFY was 2.97 t/ha in combined trial periods which is an increase by 12% (0.37t/ha) with respect to 20 kgP/ha compared to the control. It was therefore, concluded that, farmers should irrigate SAMPEA 14 using the 5 day irrigation schedule in combination with 20 kgP/ha of phosphorus fertilizer for optimum fodder yield.